The Ubiquitin-Proteasome System and Proteasome Inhibitors in Central Nervous System Diseases - Shah, Imtiaz M.; Napoli, Mario D. (Cardiovascular & Haematological Disorders - Drug Targets, 2007)
The ubiquitin-proteasome system (UPS) displays an important quality control function, by removing abnormal proteins from the cytosol, the nucleus and the endoplasmic reticulum. It controls the intracellular levels of short-lived and regulatory proteins important for a variety of basic cellular processes. The pathway involves an enzymatic cascade through which multiple 76-amino acid ubiquitin monomers are covalently attached via a three-step process to the protein substrate, which is then degraded by the 26S proteasome complex. The proteasome is a cylindrical organelle that recognizes ubiquitinated proteins, degrades a large proportion of intracellular proteins, and recycles ubiquitin. Alterations in the proteasome proteolytic pathway have been contributed to protein alterations associated with aging and, in fact, dysregulation of the UPS has been linked to several disease states including neurodegenerative diseases, malignancies, and inflammatory- related diseases. Strong preclinical data now exist supporting the use of reversible proteasome inhibitors to treat a variety of disease states including cancer, autoimmune and inflammatory diseases, myocardial infarction, and ischemic brain injury. Bortezomib (Velcade®) has recently been licensed for the treatment of patients with multiple myeloma and is also undergoing further evaluation for the treatment of chronic lymphocytic leukemia and a variety of solid tumors. MLN- 519 is a small-molecular-weight lactacystin analogue and is being studied for the potential treatment of inflammatory disease and stroke. MLN-519 has demonstrated a neuroprotective effect in rat models of middle cerebral artery occlusion reducing infarct volume, brain oedema and improves neurological outcome with a therapeutic window of up to 6-hrs. This review article focuses on the recent progress in the use of proteasome inhibitors in nervous system diseases with emphasis on the bench-to-bedside research effort which provided the foundation for clinical development of proteasome inhibitors in the treatment of neurological disorders.
Keywords: Proteasome